2003
DOI: 10.1038/sj.bjc.6600938
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of elevated level of blood midkine with poor prognostic factors of human neuroblastomas

Abstract: The heparin-binding growth factor midkine (MK) is the product of a retinoic acid-responsive gene, and is implicated in neuronal survival and differentiation, and carcinogenesis. We previously reported that MK mRNA expression is elevated in neuroblastoma specimens at all stages, whereas pleiotrophin, the other member of the MK family, is expressed at high levels in favourable neuroblastomas. As MK is a secretory protein, it can be detected in the blood. Here, we show a significant correlation of the plasma MK l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 35 publications
2
53
1
Order By: Relevance
“…As predicted from our previous data, (15) we found that MK level is correlated with established prognostic factors (MYCN, TRKA, ploidy, stage and age). Since mass screening has been discontinued, sporadic NBL are the major subject of therapy.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…As predicted from our previous data, (15) we found that MK level is correlated with established prognostic factors (MYCN, TRKA, ploidy, stage and age). Since mass screening has been discontinued, sporadic NBL are the major subject of therapy.…”
Section: Discussionsupporting
confidence: 67%
“…The data indicate close correlations between MK levels and known prognosis factors and are consistent with our previous report. (15) Figure 2(a) shows Kaplan-Meier survival curves based on plasma MK levels for all NBL cases. A high MK level was closely associated with poor prognosis of NBL patients (P < 0.0001), indicating that the MK level alone can be a prognostic factor for NBL patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, MDK was shown to correlate with tumor progression and invasiveness of neuroblastoma. Indeed, plasma MDK levels were found to be significantly correlated with the status of N-myc amplification, TRKA expression, and stage, which are known prognostic factors in neuroblastoma (19). In this study, we assessed the effects of the 81-121 deleted MDK (MDKD81-121) lacking its last 40 amino acids, and for the first time, demonstrate that this truncated protein could act as a potent inhibitor of tumor growth and angiogenesis in a neuroblastoma tumor model.…”
Section: Introductionmentioning
confidence: 99%